Immunohistochemical study of CD44 in сolorectal adenocarcinoma - Shyshkin, M. A.; Khrystenko, T. A. (Морфологія / Morphologia / Morfologìâ, 2020)
Background. Over the last decade, a significant amount of data supporting the cancer stem cell hypothesis has been accumulated. Despite the large number of works devoted to the study of the stem cell marker CD44 in colorectal adenocarcinoma, the question of the prognostic value of this marker is still controversial. Objective. To study CD44 immunohistochemical expression in colorectal adenocarcinoma on the I, II, III, IV stages (pTNM). Methods. Pathohistological and immunohistochemical studies of surgical material from 30 patients that underwent surgical treatment of colorectal adenocarcinoma (I–IV stages) were carried out. Polyclonal antibodies CD44 (CD44 Std. / HCAM Ab-4, Thermo Scientifiс, USA) were used for immunohistochemical study. Results. 16,7% of all the studied cases were stage I colorectal adenocarcinomas, 26,7% – stage II colorectal adenocarcinomas, 33,3% – stage III colorectal adenocarcinomas, and 23,3% – stage IV colorectal adenocarcinomas. It was established that colorectal adenocarcinoma is characterized by the medium membrano-cytoplasmic expression of CD44 with the median 90,49 (62,19; 110,15) CUOD that statistically significantly higher than CD44 expression level in non-changed mucosa of the distal colon. There is a tendency to increasing of expression level of the marker in sequence of the stages of colorectal adenocarcinoma development, wherein median of CD44 expression in stage II carcinomas is significantly higher than the same characteristic in stage I carcinomas (70,32 (55,13; 90,56) CUOD vs. 51,12 (31,14; 60,32) CUOD, р˂0,05), and median of CD44 expression in stage III carcinomas is significantly higher than the same characteristic in stage II carcinomas (104,76 (90,03; 112,26) CUOD vs. 70,32 (55,13; 90,56) CUOD, р˂0,05). Furthermore, correlations between CD44 expression level and depth of tumor’s invasion (r=0,48, p˂0,05), presence of regional metastases (r=0,53, p˂0,05), presence of distant metastases (r=0,38, p˂0,05), histological grade of the tumor (r=0,27, p˂0,05) were revealed. Conclusion. CD44 immunohistochemical expression increases significantly during the progression of colorectal adenocarcinoma from stage I to stage III (pTNM), as well it correlates with depth of the tumor’s invasion, presence of regional and distant metastases, and with histological grade of the tumor.